Penerapan Model Pembelajaran Contextual Teaching And Learning Dalam Membangun Karakteristik Aswaja Mata Pelajaran PAI - Anwar, Saeful; Yogi Prana Izza; Suttrisno; Rosyada Puspita Rahmawati (Yayasan Perguruan Kampus, 2024)
This research is motivated by students' lack of understanding of the material presented by the teacher in learning. This is why the teacher took the initiative to use the contextual teaching and learning model. Contextual teaching and learning is a learning model that encourages students to make connections between their knowledge and its application in everyday life. This research shows character development based on Islamic education values based on Ahlussunnah wal Jama'ah (aswaja). The purpose of this research is to find out how teachers apply and know the impact of the contextual teaching and learning model in building aswaja characteristics through Islamic religious education and ethics subjects. The research approach uses descriptive research. Based on the research that has been done, it shows that the application of the contextual teaching and learning model has five steps including the following: the teacher provides a stimulus to students, students pay attention to the pictures given by the teacher, conduct exploration, namely by students discussing a problem contained in the picture, drawing conclusions from discussions that have been carried out by students, presenting the results of group discussions. The impact received is positive, because students become more active, do not feel bored, and more easily understand the material presented by the teacher.